Cleistocalyx nervosum extract ameliorates chemical-induced oxidative stress in early stages of rat hepatocarcinogenesis - Sirinya Taya (2018)
Purpose: To study the effect of Cleistocalyx nervosum extract (CE) on diethylnitrosamine (DEN) and phenobarbital (PB) induced oxidative stress in early stages of rat hepatocarcinogenesis. Materials and Methods: Male Wistar rats were divided into 4 groups, with Group 1 as a negative control and Group 2 was a positive control receiving DEN injections once a week and PB in drinking water for 6 weeks. Two weeks before DEN initiation and PB treatment, Groups 3 and 4, were fed with 500 and 1000 mg/kg of CEs, respectively, for 8 weeks. Results: A number of GST-P-positive foci, preneoplastic lesions, in the liver were markedly increased in carcinogen administered rats, but was comparatively decreased in rats treated with 1000 mg/kg of CE. The CE reduced malondialdehyde in serum and in the livers of rats treated with DEN and PB. Moreover, CE significantly increased the activities of glutathione peroxidase and catalase in rat liver. Conclusions: CE appeared to exert its chemopreventive effects by modulating antioxidant status during DEN and PB induced early stages of hepatocarcinogenesis in rats.